CAUSES OF DECIDUOUS TEETH DISCOLORATION - O’ktamova Shaxnozabonu (Web of Journals Publishing, 2025)
This article discusses the causes of discoloration of deciduous teeth, their pathogenesis, and clinical manifestations. In children, discoloration of primary teeth is often associated with dental caries, trauma, genetic factors, and external influences. A deeper understanding of the etiological factors of tooth discoloration plays a crucial role in pediatric dentistry, particularly in the prevention, early diagnosis, and effective treatment of dental diseases in children.
Keywords: Deciduous teeth Discoloration Dental caries Pediatric dentistry Prevention